Adaptation of the sulfophosphovanillin method of analysis of total lipids for various biological objects as exemplified by Drosophila melanogaster - M. A. Eremina; N. E. Gruntenko (Вавиловский журнал генетики и селекции)
Lipid metabolism is crucial in physiology. In recent decades the model object Drosophila melanogaster has been actively used in the study of the fundamental issues of lipid metabolism and its disorders, including obesity, as well as in the search for therapeutic goals for the treatment of metabolic disorders in humans. Quick and accurate quantification of lipid content is an important step in solving these problems. For the first time the method of quantitative measurement of total lipids with the use of the sulfophosphovanillin (SPV) method was described by Zöllner and colleagues in 1962, and adapted for insects by Van Handel on females of the yellow fever mosquito Aedes aegypti. The advantages of this method compared to traditional gravimetric and chromatographic methods of analysis are the use of a small amount of biological material, lack of need for complex manipulations with the sample, its high sensitivity, reproducibility and simplicity of implementation with a minimum set of equipment. Here, a modification of the Van Handel protocol is described, which allows the method to be adapted for quantitative determination of total lipids for various organisms as exemplified a widely used model, D. melanogaster. To test the effectiveness of the modified method, we measured the content of total lipids in D. melanogaster females carrying hypomorphic mutations of the dilp6 and dfoxo insulin signaling pathway genes compared to the wild-type Canton-S line, and showed that dilp6 took part in the regulation of fat metabolism, while dfoxo did not. The results obtained emphasize the effectiveness of the colorimetric method with the use of SPV reaction and spectrophotometry for the quantitative analysis of total lipids.